Rancang Bangun Alat Pengusir Hama Burung Berbasis Arduino Uno - Syafri Maradu Manurung; Anjar Wanto; Indra Gunawan (JITEKH, 2022)
Bird pests are one of the problems that always haunt farmers, these pests often make it difficult for farmers, plus during the rice harvest period, bird pests will increase, thereby reducing the production yields that will be produced. The purpose of this study is to make an Arduino Uno-based bird repellent using an ultrasonic sensor, which is to read if a bird approaches it will automatically activate the sound that has been installed on a bird repellent that resembles a scarecrow. In addition, this tool can also move automatically if there are pests that come, the result of this study is the application of Bird Pest Repellents that can be implemented in rice fields.